Navigating resilience pathways in Laos: integrating GESI in the Agroecology Initiative - Farnworth, C.R.; Rietveld, Anne (2024)
Climate changes threaten to outpace people's adaptability and resilience. The CGIAR Initiative on Agroecology, working in Attapeu, Laos, explores how women and men are creating diverse pathways towards economic and ecological resilience, and is creating gender-transformative interventions for equitable benefits. Climate change is causing extreme weather events such as droughts and floods to occur more frequently in Laos. These shocks are profoundly impacting local livelihoods and ecosystems in harmful ways.